The Relationship Between Workload and Nurse Performance in Nursing Care Documentation: a Cross-Sectional Study - Rasu, Stella (PT FORMOSA CENDEKIA GLOBAL, 2024)
Hospitals nowadays continue to strive to improve the performance of healthcare workers, including nurses, in enhancing the documentation of nursing care. Indirectly, the excessive workload of nurses often becomes an obstacle in documenting nursing care. This study aims to analyze the relationship between workload and nurses' performance in documenting nursing care. The type of this research is a quantitative study that is observationally analytical using a cross-sectional design. The research sample consisted of 36 nurses using a total sampling technique. Data analysis involved univariate and bivariate analysis. The results of the study obtained a p-value of 0.000, which means there is a relationship between workload and nurses' performance in documenting nursing care. The conclusion of this study is that there is a relationship between workload and nurse performance in documenting nursing care in the General Inpatient Ward of Budi Setia Langowan Hospital. The recommendation in this study is aimed at nurses to use the study results as a learning material for head nurses to manage the workload of each nurse so that it is not excessive, allowing for proper documentation of nursing care.